ANALYSIS OF PREMIUM INCOME, INVESTMENT RESULTS AND UNDETWRITING RESULTS ON PROFIT (CASE STUDY AT PT. ASURANSI BANGUN ASKRIDA) - Masriza Masriza; Gita Sari Gustika; Hasanah Yaspita; Dewi Hartika (JURNAL MANAJEMEN DAN BISNIS, 2022)
This research was conducted at PT. Asuransi Bangun Askrida. Just like in other financial institutions in general, insurance companies are required to sharpen the direction so that the vision and mission of insurance can be achieved. One strategy to achieve this vision is to improve the company's financial performance. PT. Asuransi Bangun Askrida with a partner motto in the business of protecting in grief, Askrida offers complete and intelligent insurance protection as well as reliable and trustworthy. In addition to receiving premiums as one of the company's sources of income, the company also makes investments, the results of which are to offer insurance programs for both the public and the company. This is because apart from its business activities that provide protection to the public, insurance is also an institution that raises funds sourced from receiving insurance premiums from the public. Underwriting results are also profit-maximizing activities through risk acceptance which is expected to generate profits. Recognition of premium income and investment returns as well as underwriting results obtained in a certain period will determine the profit of the insurance company. This study aims to analyze the effect of premium income, investment returns and underwriting results on profits. This study uses secondary data and multiple regression analysis. The targeted output in this research is publish disinta 3 or 4.